THEORETICAL BASICS OF THE FORMATION OF READINESS FOR PEDAGOGICAL DESIGN IN FOOTBALL COACHES (Physical Culture and Sport: Scientific Perspective, 2023)
The article draws attention to the conformity of the modernized descriptors of the National Framework of Qualifications with the modern existentially oriented philosophy of education. Philosophical and psychological-pedagogical principles of formation of readiness for pedagogical design among football coaches are clarified and formulated.Correspondence of various philosophical ideas to various types of educational philosophy of trainers is emphasized: traditional educational perennialism of the trainer – idealistic philosophy; educational essentialism - his realistic worldview; educational progressivism - philosophies of pragmatism; educational reconstructionism - philosophies of existentialism.Existentialism is considered as a modern philosophical theoretical basis for the formation of the readiness of reconstructionist coaches for pedagogical design - the professional intention to apply the interactive method in football and game design of matches, in the development of football culture and the acquisition of levels of specialized sports education. The existential coach creates the conditions for choosing his own development trajectory by each football player of the team by means of pedagogical design.• Gardner's theory of "multiple intelligence" is defined as a psychological and pedagogical theoretical basis for the trainer's readiness for pedagogical design. The components of the "multiple intelligence" of a football coach are singled out: practical, emotional, verbal. The components of V. Klymenko's "mechanism of sports creativity" are indicated: psychomotor skills, energy potential, criticality and their correspondence to the components of "multiple intelligence". The practical component and psychomotor skills are described in detail as priority for the creative "multiple intelligence" of a modern football coach.
Keywords: philosophy of education; methodological principles; pedagogical design; football coaches; multiple intelligence